PEMBERDAYAAN LANSIA TERLANTAR MELALUI PROGRAM ISTANA LANSIA SERAMBI MADINAH DINAS SOSIAL KOTA SOLOK - shyntia wahyuni; Wanda Fitri; Muhammad Fauzi (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2023)
Neglected elderly are one of the people with social welfare problems which are important to overcome. Considering that the elderly population is quite large and the number of abandoned elderly is increasing, the government's help and assistance is needed. The government, through social services, has an empowerment program that is suitable for dealing with neglected elderly problems related to physical, psychological, social and economic aspects. This study aims to look at strategies for empowering neglected elderly people through the Serambi Medina Elderly Palace program. This research is qualitative research with a descriptive analysis approach. Information and data from informants were obtained through observation and interviews. Data analysis techniques through data collection methods, data reduction and drawing conclusions. The results of the research show that; 1) Enabling companions provide motivational encouragement or enthusiasm for the elderly, there is fulfillment of the needs of the elderly, as well as information disclosure for the elderly. 2) Empowering, the elderly have been provided with facilities such as the existence of supporting facilities and infrastructure, health services, cooking training and the availability of funding institutions. 3) Protecting the elderly who are enrolled in the Serambi Medina Elderly Palace program have been protected by protection, regulations and special attention from the government and related agencies.